Association of interferon gamma inducible protein-10, monocyte chemoattractant protein-1, macrophage inflammatory protein-1 alpha, interleukin-6, and rs12252 single nucleotide polymorphism of interferon-induced transmembrane protein-3 gene with the severity of COVID-19 infection - Shafia Mulla; Md.Maruf Ahmed Molla; S. M. Ali Ahmed; A. K. M. Akhtaruzzaman; Ahmed Abu Saleh; Shaheda Anwar (SpringerOpen, 2022)
Abstract Background Evaluating the serum levels of IP-10, MCP-1, MIP-1α, and IL-6 and genotyping of rs12252 SNP of IFITM3 gene among different categories of COVID-19 patients might aid in understanding the pathogenesis of COVID-19 and contribute to developing disease-specific biomarkers and therapeutic strategies. Methods This is a cross-sectional study involving a total of 84 COVID-19 patients confirmed by positive RT-PCR and 28 healthy controls. COVID-19 patients were recruited from the intensive care unit (ICU) and COVID unit of Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka. COVID-19 patients were categorized into moderate, severe, and critically ill groups according to the World Health Organization classification. The serum IP-10, MCP-1, and MIP-1α levels were measured by cytometric bead array assay by flow cytometry, and serum IL-6 level was detected by the chemiluminescence method. rs12252 SNP of the IFITM3 gene was detected by polymerase chain reaction-restriction fragment length polymorphism (PCR RFLP). Results The serum IP-10, MCP-1, MIP-1α, and IL-6 levels among critically ill COVID-19 patients were significantly higher than that in patients with moderate disease and healthy controls (p < 0.001). Genotype distribution for rs12252 (42 T/C) SNP of the IFITM3 gene between the different groups of COVID-19 patients and healthy controls showed that CC genotype was statistically associated with disease severity (p < 0.001). Conclusions IP-10 and MCP-1, MIP-α, IL-6, and CC genotype of rs12252 (42 T/C) SNP of IFITM3 gene are associated with COVID-19 severity.